THE EFFECT OF THE ACIDITY OF FERMENTED MILK AGAINST THE HARDNESS OF NANOHYBRID COMPOSITE RESIN - Hanny Tiara A Sinaga; Diah Ajeng Purbaningrum; Ariosta Ariosta; Dwi Retnoningrum (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background : The hardness of nanohybrid composite resin can decrease due to the acidic condition of the oral cavity. The acidic condition of the oral cavity can cause continuous degradation in composite resin. Fermented milk is a beverage that is widely sold in the market and is good for consumption however this beverage has the acid potential of hydrogen (pH) which can reduce the composite resin toughness. Aim : To determine the acidity effect of fermented milk on the hardness of nanohybrid composite resin. Method: Experimental study with a post test control group design. There were 27 samples of nanohybrid composite resin. One time immersion for three seconds in each group of beverages namely Milk, Cimory, and Yakult. After 15 days, a composite resin hardness test was performed using a Micro Vickers Hardness Tester with a load of 100 grams for 10 seconds. Statistical tests using One Way ANOVA. Results: The nanohybrid composite resin exhibited significant reduction in hardness between three beverage groups. Post hoc LSD test showed that there were significant differences between Milk with Yakult (p = 0.006) and Cimory with Yakult (p = 0.008) while Milk with Cimory (p = 0.907) did not have significant. Conclusions : There is a effect of fermented milk influences the hardness. There is a significant difference between Milk and Yakult and between Cimory and Yakult and there is no significant difference between Milk and Cimory.